2020
DOI: 10.3906/sag-2008-32
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and pharmacological roles of melatonin in the pathophysiological components of cellular injury after ischemic stroke

Abstract: Apart from its metabolic or physiological functions, melatonin has a potent cytoprotective activity in the physiological and pathological conditions. It is synthetized by the pineal gland and released into the blood circulation but particularly cerebrospinal fluid in a circadian manner. It can also easily diffuse through cellular membranes due its small size and lipophilic structure. Its cytoprotective activity has been linked to its potent free radical scavenger activity with the desirable characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Here, we observed that iNOS levels were enhanced after sole caffeine injection, similar to the previous results, while L -theanine and Mg-T injection after caffeine administration recovered that effect and reversed the increased iNOS levels. Given that hypoxic conditions such as stroke induce synthesis of NO by iNOS and this leads to exacerbation of the injury ( 64 ), Mg- L -theanine compounds may help reduction of inflammation by their anti-inflammatory role.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed that iNOS levels were enhanced after sole caffeine injection, similar to the previous results, while L -theanine and Mg-T injection after caffeine administration recovered that effect and reversed the increased iNOS levels. Given that hypoxic conditions such as stroke induce synthesis of NO by iNOS and this leads to exacerbation of the injury ( 64 ), Mg- L -theanine compounds may help reduction of inflammation by their anti-inflammatory role.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin, an endogenous regulator, is a metabolite of tryptophan released from the pineal gland ( 213 ). It is involved in numerous physiological and pathophysiological processes including antioxidant ( 214 ), anti-apoptotic, and anti-inflammatory effects ( 215 ). Melatonin is of neuroprotective effect, which reduces infarct volume, lowers brain edema, and increases neurological scores.…”
Section: Drugs That Target Mitochondriamentioning
confidence: 99%
“…A multitude of different pathways have been associated with melatonin's protection on neurological damage, including maintaining Ca 2þ homeostasis (Onaolapo et al, 2019), decreasing oxidative stress (Watson et al, 2016), and attenuating endoplasmic reticulum stress (Lin et al, 2018). Melatonin was reported to play important roles in the pathophysiological components of cellular injury after ischemic stroke via modulating oxidative stress, mitochondria, apoptosis, inflammatory response, melatonin receptors 1/2, circular RNA in ischemic injury (Kilic et al, 2020). For example, in a focal cerebral ischemic injury rat model, melatonin reduced brain infarction associated with sequentially rescued neuronal apoptosis and attenuated neuroinflammatory response by modulating oxidative stress signaling (NF-jB/COX2/iNOS) and enhancing anti-oxidative systems such as Nrf2/HO-1/Trx (Ling et al, 2020).…”
Section: Discussionmentioning
confidence: 99%